New specimens of horned dinosaurs from the Aguja Formation of West Texas, and a revision of Agujaceratops. (3rd August 2017) - Lehman, Thomas M.; Wick, Steven L.; Barnes, Kenneth R.
Abstract : Most horned dinosaur remains recovered from the Aguja Formation in West Texas are referable to the endemic chasmosaurine Agujaceratops mariscalensis . One specimen, however, differs sufficiently to justify its designation as the holotype of a new species, Agujaceratops mavericus sp. nov. This specimen and an isolated postorbital horncore from the same vicinity are stratigraphically the highest found in the Aguja Formation. A well-preserved juvenile specimen exhibits some unique features, and others compatible with A. mavericus, but due to its immature condition cannot be identified with certainty. A parietal referred to A. mariscalensis is the most complete thus far known, and shows that the frill of this taxon is more elaborately ornamented than previously believed, bearing a set of large horn-like spikes at the posterolateral corners. These two species share features of the premaxilla and squamosal, which warrant their inclusion in the same genus. However, characters thought to distinguish the two species vary in a manner similar to that found in other chasmosaurines, where debate persists as to their taxonomic significance. A consensus species concept has yet to be adopted for ceratopsid genera, of which most are monotypic. As a result, the two Agujaceratops species could be interpreted as arbitrary anagenetic stages in a single lineage, end-members in a spectrum of ontogenetic and sex-associated variation in that lineage, or two sympatric lineages that occupied separate niches in the same range. http://zoobank.org/urn:lsid:zoobank.org:pub:1846D524-AC7F-4126-8787-33B26D80CF52